Identification and characterization of a UbK family kinase in Porphyromonas gingivalis that phosphorylates the RprY response regulator. (19th July 2021) - Perpich, John D.; Yakoumatos, Lan; Johns, Parker; Stocke, Kendall S.; Fitzsimonds, Zackary R.; Wilkey, Daniel W.; Merchant, Michael L.; Miller, Daniel P.; Lamont, Richard J.
Abstract: Phosphorylation of proteins is a key component of bacterial signaling systems that can control important functions such as community development and virulence. We report here the identification of a Ubiquitous bacterial Kinase (UbK) family member, designated UbK1, in the anaerobic periodontal pathogen, Porphyromonas gingivalis . UbK1 contains conserved SPT/S, Hanks‐type HxDxYR, EW, and Walker A motifs, and a mutation analysis established the Walker A domain and the Hanks‐type domain as required for both autophosphorylation and transphosphorylation. UbK1 autophosphorylates on the proximal serine in the SPT/S domain as well as the tyrosine residue within the HxDxYR domain and the tyrosine residue immediately proximal, indicating both serine/threonine and tyrosine specificity. The orphan two‐component system response regulator (RR) RprY was phosphorylated on Y41 in the receiver domain by UbK1. The ubk1 gene is essential in P. gingivalis ; however, overexpression of UbK1 showed that UbK1‐mediated phosphorylation of RprY functions predominantly to augment its properties as a transcriptional enhancer. These results establish that P. gingivalis possesses an active UbK kinase in addition to a previously described Bacterial Tyrosine family kinase. The RR RprY is identified as the first transcriptional regulator controlled by a UbK enzyme.